Ships, swindlers, and scalded hogs : the rise and fall of the Crooker Shipyard in Bath, Maine - Hill, Frederic B. (Down East, 2016)
"A history of the shipbuilding company of William Donnell Crooker and Charles Crooker discussing the family, its contributions to shipbuilding, and the historic sweep of shipbuilding in the area"--Provided by publisher